Penerapan Filtrasi Anaerobik di Masjid Sungai Geneng, Lamongan - Tamimah, Ni'matut; Sa’diyah, Aminatus; Azis Ramadani, Tarikh; Luluk Kusminah, Imah; Puspita Sari, Devina; Trisna Nugraha, Anggara; Mahardhika, Pekik (Jurnal Cakrawala Maritim, 2025)
Many areas in Indonesia still have water sources that are unsuitable for daily use. One such area is the vicinity of Sungai Geneng Mosque, Kembang Bahu District, Lamongan Regency. In this area, the water source contains high levels of lime and organic materials, making it unsuitable for consumption. To address this issue, the Corporate Social Responsibility (CSR) Team from Politeknik Perkapalan Negeri Surabaya (PPNS) implemented a water filtration application in the area. The filtration method used is the anaerobic filtration system. Based on the filtration results, high levels of lime were successfully reduced to meet health standards, making the water clean and safe for consumption. Additionally, the organic materials in the water were converted into biogas, which serves as an alternative energy source for cooking and environmentally friendly vehicles.